2020
DOI: 10.3389/fbioe.2020.01001
|View full text |Cite
|
Sign up to set email alerts
|

Synergy Screening Identifies a Compound That Selectively Enhances the Antibacterial Activity of Nitric Oxide

Abstract: Antibiotic resistance poses a serious threat to global health. To reinforce the antiinfective arsenal, many novel therapeutic strategies to fight bacterial infections are being explored. Among them, anti-virulence therapies, which target pathways important for virulence, have attracted much attention. Nitric oxide (NO) defense systems have been identified as critical for the pathogenesis of various bacteria, making them an appealing therapeutic target. In this study, we performed chemical screens to identify i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Looking forward, understanding the mechanistic bases of prioritized detoxification could lead to strategies to treat bacteria that use NO and H 2 O 2 detoxification systems to enhance their virulence [ 9 ]. Such an anti-infective approach is currently being explored [ 35 ], along with other alternative treatments [ 36 40 ], with the ultimate goal of complementing currently available antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Looking forward, understanding the mechanistic bases of prioritized detoxification could lead to strategies to treat bacteria that use NO and H 2 O 2 detoxification systems to enhance their virulence [ 9 ]. Such an anti-infective approach is currently being explored [ 35 ], along with other alternative treatments [ 36 40 ], with the ultimate goal of complementing currently available antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The outer membrane of Gram-negative bacteria is a major barrier for entry of many antibiotics otherwise active against Gram-positive bacteria. While we observed no activity of achromonodin-1 against wild-type E. coli MG1655, we observed single-digit micromolar (MIC of 2.5 μM) activity against the E. coli imp4213 strain (Figure S14), a mutant strain with increased permeability of the outer membrane. Other RNAP-inhibiting lasso peptides cross the inner membrane via the proton gradient powered SbmA in E. coli , or the ABC transporter YddA in Burkholderia …”
Section: Resultsmentioning
confidence: 84%
“…As a result of this genetic defect, the outer leaflet of the OM of this strain is irregularly enriched in phospholipids, which in turn leads to enhanced permeability of compounds normally excluded. Previous studies have employed the use of this strain for toxicity screens of compounds so that the OM barrier plays a minimal role in the screen. We found that cloacaenodin, when applied extracellularly in a spot-on-lawn assay, had no activity against E. coli MC4100 (Figure A), but it had potent, low micromolar activity (MIC ≤ 1.9 μM) against E. coli imp4213 (Figure B).…”
Section: Resultsmentioning
confidence: 91%